Clickbait and translation: Proposing a typology of online news headline transcreation strategies - Untari, Lilik; Purnomo, SF. Luthfie Arguby; Purnama, SF. Lukfianka Sanjaya; Giyoto, Giyoto (Universitas Syiah Kuala, 2023)
Clickbait has been widely studied within the online news headline context; however, it is still understudied under the umbrella of transcreation. By employing the theory of transcreation by Gaballo (2012) and news headline tabloidization/clickbaiting presentation by Reinemann et al. (2012) on a corpus of online news headlines in a qualitative research design, we argued that news headline is transcreated for a clickbaiting purpose through the use particular linguistic features as the strategies. Those linguistic features are bombasting, referencing, and bamboozling. The first refers to the use of high-sounding or hyperbolic expressions, the second to popular references, and the last to multi-interpretable expressions. Each of the three transcreation strategies has what we call the degree of transferability. Through the degree of transferability, whether or not a translated online news headline might fall into the category of translation, transcreation, or in between could be revealed. The degrees of transferability might also reveal how bombasting, referencing, and bamboozling influence the categorization. The findings of the study could be employed as a guideline for news translation scholars and practitioners in reviewing and assessing the translation of online news headlines regarding the tendency of the tabloidization use in the clickbait context. Future studies could address the issues of the identities of news sites, news sites, and news readers as a parameter in assessing the quality of news headline translation or transcreation.